Uk GAAP / Generally Accepted Accounting Practice in the United Kingdom: Fifth Edition - Davies Mike; Macmillan; Paterson Ron; Wilson Allister (1997)
This reference book reflects the many changes which have taken place in the UK financial reporting environment over the past three years. The Development of the UK GAAP, The Quest for a Conceptual Framework for Financial Reporting, Revenue Recognition, Corporate Governance and the OFR, Consolidated Accounts, Business Combinations and Disposals, Associates and Joint Ventures, Foreign Currencies, Financial Instruments, Fixed Assets and Depreciation, Investments, Research and Development, Capitalization of Borrowing Costs, Stocks and Long-Term Contracts, Capital Instruments, Off Balance Sheet Transactions, Leases and Hire Purchase Contracts, Government Grants, Segmental Reporting, Pension Costs, Taxation, Reporting Financial Performance, Earnings Per Share, Post Balance Sheet Events, Contingencies, Provisions, Cash Flow Statements, Related Parties, Directors' and Officers' Loans and Transactions, Directors' Remuneration, Interim Reporting, Specimen Financial Reporting, Appendix: Specimen Financial Statements, Index of Extracts from Accounts, Index of Statutes and Standards, Index.